Reimagining the First Amendment: The Assembly Clause as a substantive right. Issue 1 (3rd July 2019) - McGravey, Kevin
ABSTRACT: The right to protest is central to democratic participation. This essay suggests that recent attempts to use the right to assemble as a doctrinal hook to better protect protest are correct but incomplete. Such attempts rightly suggest that the Court's current approach through free speech inadequately protects protest directed at public officials. But this essay argues that such accounts and the Court's jurisprudence also inadequately protect citizens' privacy in public spaces. By looking at current cases, history and theory it proposes an alternative account of assembly that better protects participation and the equality necessary to make participation effective.